Konsep Pariwisata Hijau Bagi Pemulihan Model Pariwisata Indonesia Pasca Pandemi Covid-19 - Ika Sri Hastuti; Melaty Anggraini; Imam Budiman (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study examines Indonesia's tourism strategy after the Covid 19 Pandemic, where the Indonesian tourism sector has experienced a decrease in economic income due to the Covid 19 pandemic. It requires closing all tourist destinations to prevent the spread of the Covid 19 virus. After the pandemic or entering the "new normal after pandemic" period, which allows every country that has entered the green zone or entered the safe level and successfully overcome the spread of COVID 19 can open its tourism sector again but emphasizes more outdoor tourist destinations that remain compliant with health and social distancing protocols. This research uses qualitative research that allows and understands the problem of deepening the strategy of eco-green or green tourism. This study aims to find out how to manage tourism and the right design for Indonesia after the Covid-19 pandemic, which emphasizes the development of the green tourism industry by WHO rules to restore the Indonesian economy to the tourism sector.